PENGARUH SIKAP, PROMOSI, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PENGGUNA KARTU KREDIT PT. BANK MEGA TBK DI MAKASSAR - Nur Nubli Cakramalinda; Jusni Jusni; Abdul Razak Munir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
This study aims to determine the influence of attitudes, promotions, and quality of service to the decision of credit card users PT. Bank Mega Tbk In Makassar. The approach used in this research is quantitative approach with the aim of studying the research naturally about the influence of attitude, promotion, and consumer service with the decision of credit card usage of PT. Bank Mega Makassar. In this study, researchers are not directly involved in the situation and setting of phenomena to be studied, this is because in this study the phenomenon that occurs in the subject of this study will be poured in the form of questionnaires. The result of the research shows that partially attitude and quality of card service have positive effect to credit card user decision. While promotion of credit card user decisions is negative and not significant.